IDENTIFIKASI MODEL KENAIKAN NILAI LAHAN DI SEKITAR GERBANG TOL SOREANG, JALAN TOL SOREANG-PASIRKOJA, BERBASIS LAND VALUE CAPTURE DENGAN MEKANISME HEDONIC PRICE MODEL - Sobari, Ahmad
The construction of toll roads aims to improve the accessibility and connectivity of an area to other areas to increase the existence of the region which has an impact on the economy in the region. The Soreang-Pasirkoja toll road is one of the toll roads in Indonesia, with the starting point in Soreang District, Bandung Regency and ending in Pasirkoja, Bojongloa Kaler District. The existence of this toll road is estimated to be able to have an impact on changes in land values, especially residential land, around existing toll gates and one of them is the Soreang Toll Gate by increasing the attractiveness of land in Soreang District. The increase in land value that occurs can be used by the government as an alternative to financing the development or maintenance of transportation infrastructure. To be able to capture the increase in the value of residential land, you can use the Land Value Capture (LVC) method with the Hedonic Price Model mechanism whose final result is a regression model between the dependent variable (NJOP or Market Price) and the independent variable (accessibility characteristics, internal and external land). Therefore, this study aims to model the increase in land value around the Soreang Toll Gate based on the characteristics of accessibility, internal land, and external land. Based on the regression model formed, the existence of the Soreang Toll Gate only affects increasing land value in terms of market prices. In addition, there are also other accessibility variables and external land variables (Distance to Activity Center and Distance to Government Center) which have a significant influence on the increase in land value (NJOP and Market Price).